Examining tissue composition, whole-bone morphology and mechanical behavior of GorabPrx1 mice tibiae: A mouse model of premature aging. (8th December 2017) - Yang, Haisheng; Albiol, Laia; Chan, Wing-Lee; Wulsten, Dag; Seliger, Anne; Thelen, Michael; Thiele, Tobias; Spevak, Lyudmila; Boskey, Adele; Kornak, Uwe; Checa, Sara; Willie, Bettina M.
Abstract: Gerodermia osteodysplastica (GO) is a segmental progeroid disorder caused by loss-of-function mutations in the GORAB gene, associated with early onset osteoporosis and bone fragility. A conditional mouse model of GO ( Gorab Prx1 ) was generated in which the Gorab gene was deleted in long bones. We examined the biomechanical/functional relevance of the Gorab Prx1 mutants as a premature aging model by characterizing bone composition, tissue-level strains, and whole-bone morphology and mechanical properties of the tibia. MicroCT imaging showed that Gorab Prx1 tibiae had an increased anterior convex curvature and decreased cortical cross-sectional area, cortical thickness and moments of inertia, compared to littermate control (LC) tibiae. Fourier transform infrared (FTIR) imaging indicated a 34% decrease in mineral/matrix ratio and a 27% increase in acid phosphate content in the posterior metaphyseal cortex of the Gorab Prx1 tibiae (p < .05), suggesting delayed mineralization. In vivo strain gauge measurement and finite element analysis showed ∼two times higher tissue-level strains within the Gorab Prx1 tibiae relative to LC tibiae when subjected to axial compressive loads of the same magnitude. Three-point bending tests suggested that Gorab Prx1 tibiae were weaker and more brittle, as indicated by decreasing whole-bone strength (46%), stiffness (55%), work-to-fracture (61%) and post-yield displacement (47%). Many of these morphological and biomechanical characteristics of the Gorab Prx1 tibia recapitulated changes in other animal models of skeletal aging. Future studies are necessary to confirm how our observations might guide the way to a better understanding and treatment of GO.